ZrO2 / γ-Al2O3 composite carrier and preparation method thereof, selective hydrodesulfurization catalyst and application thereof
By using technical means such as ZrO2/γ-Al2O3 composite carrier and heteroatomic zirconium, the problems of harsh reaction conditions and large hydrogen consumption during the diesel hydrodesulfurization process were solved, and efficient direct desulfurization was achieved, which was in line with the National VI clean diesel standard.
Patent Information
- Application Number
- CN202111681464.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-12-31
AI Technical Summary
During the existing diesel hydrodesulfurization process, there are problems such as harsh reaction conditions, long reaction routes, and large hydrogen consumption, making it difficult to effectively remove sulfur from complex sulfides.
Using ZrO2/γ-Al2O3 composite support as catalyst support, the introduction of heteroatom zirconium and sucrose to form a composite support with high specific surface area and pore volume. Combining MoO3 and NiO as active components, the selective hydrodesulfurization activity of the catalyst is improved. .
It improves the direct desulfurization (DDS) selectivity of the catalyst, reduces the harshness of the reaction and hydrogen consumption, and can effectively remove sulfur and polycyclic aromatic hydrocarbons in diesel. The product meets the National VI Clean Diesel Standard.
Smart Images

Figure CN116408055B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of petroleum refining and hydrofining, and in particular to a method for preparing a zirconium-aluminum composite carrier, a selective hydrodesulfurization catalyst using the composite carrier as a carrier, and the application of the selective hydrodesulfurization catalyst. Background Art
[0002] The increasing deterioration of crude oil and increasingly stringent environmental protection requirements have made diesel processing increasingly difficult. Under the current situation where the total supply of domestic diesel market exceeds the total demand, how refineries can speed up the upgrading of diesel quality, reduce the production cost of oil products, and produce high-quality clean diesel is one of the key tasks of refining and chemical enterprises.
[0003] The current measures to upgrade the quality of existing diesel hydrotreating units include increasing the severity of the unit reaction, reducing the unit processing capacity, reducing the diesel terminal distillation point, and using highly active diesel hydrotreating catalysts. Increasing the severity of the unit reaction, reducing the unit processing capacity, and reducing the diesel terminal distillation point have an adverse impact on the production cost and production efficiency of the unit. In order to solve the above problems, foreign companies such as Exxon Mobil, Criterion, Akzo Nobel, IFP, and Haldor have adopted a series of measures to improve the quality of diesel hydrotreating units. UOP and other companies have developed highly active hydrogenation catalysts suitable for deep hydrodesulfurization of diesel and have achieved wide application. Therefore, the development and application of highly active diesel hydrogenation catalysts is the most effective measure for diesel hydrogenation units to upgrade diesel quality, which is in line with the development trend of world refining technology.
[0004] At present, the main starting point for improving the efficiency of hydrodesulfurization is to improve the supporting technology, modify the catalyst and develop new catalysts. Compared with the first two, it is easier to develop new catalysts. Alumina, as a traditional hydrodesulfurization catalyst carrier, has the characteristics of high specific surface area and high thermal stability, but alumina is an inert carrier, and its activity and anti-toxicity still need to be improved. Zirconium dioxide, as an important structural functional material, has the characteristics of high temperature resistance, high hardness, good chemical stability and thermal stability, and is widely used in structural ceramics, sensors, solar cells, thermal insulation materials and other fields. Zirconium dioxide is easy to produce oxygen vacancies and can have unique interactions with active components, so it is also a distinctive catalyst carrier. Catalysts with zirconium oxide as the carrier show unique advantages compared with conventional carriers, such as good sulfur resistance and easy reduction of the supported metal. However, the conventional zirconium dioxide carrier has a small specific surface area, underdeveloped pores, and irregular changes in pore size, which limits its excellent performance.
[0005] Patent CN00123133.2 discloses a zirconium-containing alumina carrier and its preparation method, wherein the zirconium-containing alumina carrier is prepared by adding a zirconium-containing compound in the form of wet nevus during the carrier molding process; the carrier has a lateral pressure strength of 12 to 24 N / mm and an infrared acidity of 0.25 to 0.30 mmol / g. This invention prepares a composite carrier in the form of wet nevus, which is highly random. The zirconium-containing compound is introduced into the alumina through a wet kneading process, which is not conducive to the uniform dispersion of the zirconium-containing compound and has an adverse effect on the hydrodesulfurization activity of the catalyst.
[0006] Patent CN201310524738.3 discloses a diesel hydrodesulfurization and denitrification catalyst and its preparation method. The catalyst comprises a carrier, an additive, and an active metal. The carrier is an Al2O3-ZrO2-TiO2-SiO2 multi-oxide composite carrier. The additive is phosphorus. Nickel, cobalt, molybdenum and tungsten are active components. The weight percentage content of each component based on the catalyst is as follows: in terms of oxide, cobalt oxide 1-6wt%; nickel oxide 1-15wt%, molybdenum oxide 2-12wt%, tungsten oxide 12-35wt%, and additive phosphorus pentoxide 1.5-5wt%; the pore volume of the catalyst is ≮0.2ml / g, and the specific surface area is ≮140m 2 / g, mechanical strength ≮15N / mm; the proportion of each component in the composite carrier is: titanium oxide accounts for 2-15wt%, silicon oxide accounts for 2-20wt%, zirconium oxide accounts for 5-15wt%; the balance is aluminum oxide. The preparation of the composite carrier of the invention is to uniformly mix pseudo-boehmite, zirconium nitrate, metatitanic acid (or nano-sized titanium dioxide or tetra-n-propyl titanate) and silica sol, then add a peptizing agent, an extrusion aid and a pore-enlarging agent to mix and knead, and then extrude into strips, and then dry and calcine to obtain an Al2O3-ZrO2-TiO2-SiO2 multi-oxide composite carrier. The preparation of the composite carrier of the invention adopts wet kneading, which is not conducive to the uniform dispersion of zirconium-containing compounds and has an adverse effect on the hydrodesulfurization activity of the catalyst.
[0007] CN201010514168.6 discloses a method for preparing a zirconium oxide-aluminum oxide composite oxide carrier, which adopts a method of preparing aluminum hydroxide sol and zirconium-containing sol in advance, introduces silicon when aluminum hydroxide is colloided, and adds a surfactant or an organic solvent to the zirconium-containing sol; after adjusting the pH values of the two colloids respectively, the two are mixed, aged, washed, filtered and dried to obtain a zirconium oxide-silicon oxide-aluminum oxide composite oxide dry gel. Then, a binder, an extrusion aid, a peptizing agent and an auxiliary agent are added to the composite oxide dry gel, and after kneading and extruding, the composite oxide carrier is obtained by drying and calcining. Among them, the binder is small-pore alumina, and the amount used is 5 to 30wt% of the weight of the composite oxide carrier. The preparation process of this invention is complicated. In order to improve the dispersibility of the sol, a surfactant or an organic solvent needs to be added to the zirconium-containing sol, and there are many factors affecting the preparation process. In addition, adding small-pore alumina as a binder during the molding process of the composite oxide carrier affects the physical properties of the carrier, thereby having an adverse effect on the hydrodesulfurization activity of the catalyst.
[0008] CN201710329054.6 discloses a composite catalyst carrier containing zirconium oxide, its preparation method and application, the composite carrier is composed of zirconium oxide, zinc oxide and manganese oxide, and the carrier contains 10-60% zirconium oxide, 15-55% zinc oxide and 15-55% manganese oxide based on 100% carrier mass. The composite carrier is prepared by a coprecipitation method, and the precipitate mixture is aged at 80-140°C for 30 minutes, filtered, dried and calcined. The catalyst prepared by impregnating the composite carrier with K and Pd is used in the reaction of synthesizing isobutanol from synthesis gas.
[0009] CN201110134042.0 discloses an alumina-zirconia composite carrier and a preparation method thereof. Based on 100% carrier mass, the carrier contains 1-95% alumina and 5-99% zirconium oxide, and the carrier has the following physical properties: bulk density 0.8-1.1 g / ml, pore volume 0.3-0.6 ml / g, specific surface area 5-60 m 2 / g, average pore size 80-350nm, preferably 100-250nm; the carrier shows double peaks at 90-140nm and 250-500nm. The invention also discloses a preparation method of the carrier and a hydrogenation catalyst containing the carrier. Patent CN201110267805.9 discloses an alumina-zirconia-titania composite carrier and a preparation method thereof. Based on 100% carrier mass, the carrier contains 1-95% alumina, 5-60% zirconium oxide, and 5-60% titanium oxide. The carrier has the following physical properties: bulk density 0.7-1.1g / ml, pore volume 0.2-0.6ml / g, specific surface area 3-60m 2 / g, average pore size 50-300nm; the carrier has double peaks at 40-120nm and 200-400nm. The invention also discloses the preparation method of the carrier and the hydrogenation catalyst containing the carrier. The above two catalysts prepared from the zirconium-containing composite carrier are both used in the reaction of carbon dihydrogenation.
[0010] The most difficult compound to remove during diesel hydrodesulfurization is 4,6-dimethyldibenzothiophene (4,6-DMDBT). The hydrodesulfurization pathways for thiophene sulfides generally include hydrodesulfurization (HYD) and direct desulfurization (DDS). Compared with the DDS pathway, the HYD pathway has problems such as harsh reaction conditions, a longer reaction route, more intermediates, and high hydrogen consumption. The reason for the different pathways is the different adsorption modes of sulfides. Complex sulfides with strong steric hindrance effects of substituents, such as 4,6-DMDBT, must first undergo hydrogenation saturation of the benzene ring through flat adsorption to weaken the steric hindrance of the sulfide, and then react via the HYD pathway. Compared with the HYD pathway, the DDS pathway desulfurizes through endpoint adsorption, and has the advantages of low hydrogen consumption and low severity.
[0011] Therefore, how to increase the proportion of reactions carried out via the DDS pathway during diesel hydrodesulfurization is of great significance to diesel hydrodesulfurization. Summary of the invention
[0012] The main purpose of the present invention is to provide a ZrO2 / γ-Al2O3 composite carrier and its preparation method, a selective hydrodesulfurization catalyst and its application, so as to overcome the defects of the prior art of diesel hydrodesulfurization, such as harsh conditions, long reaction route and high hydrogen consumption.
[0013] In order to achieve the above object, the present invention provides a method for preparing a ZrO2 / γ-Al2O3 composite carrier, comprising the following steps:
[0014] Step 1, mixing zirconium oxychloride and water to obtain a zirconium-containing solution;
[0015] Step 2, adjusting the pH value of the zirconium-containing solution to alkaline, stirring, and aging;
[0016] Step 3, separating the aged material obtained in step 2 to obtain a solid, and washing to remove Cl in the obtained solid. - , obtaining a zirconium-containing hydrogel;
[0017] Step 4, mixing sucrose, pseudo-boehmite, the zirconium-containing hydrogel and water, heating, and acid-lyzing to obtain zirconium-aluminum sol;
[0018] Step 5, adjusting the pH value of the zirconium-aluminum sol to alkaline, aging, then washing with water to neutrality, solid-liquid separation, and vacuum freeze-drying to obtain a zirconium-aluminum composite material;
[0019] Step 6: Mix the zirconium-aluminum composite material with an additive, and shape it to obtain a ZrO2 / γ-Al2O3 composite carrier.
[0020] The preparation method of the ZrO2 / γ-Al2O3 composite carrier of the present invention comprises the following steps: the concentration of the zirconium-containing solution in step 1 is 0.18-0.24 mol / L; and the pH value of the zirconium-containing solution is adjusted to 9-10, and the adjusting reagent is ammonia water.
[0021] The preparation method of the ZrO2 / γ-Al2O3 composite carrier described in the present invention, wherein the added amount of sucrose is 5 to 15wt% of the weight of the ZrO2 / γ-Al2O3 composite carrier; the added amount of the pseudo-boehmite calculated as alumina is 80 to 95wt% of the weight of the ZrO2 / γ-Al2O3 composite carrier, and the added amount of the zirconium oxychloride calculated as zirconium dioxide is 5 to 20wt% of the weight of the ZrO2 / γ-Al2O3 composite carrier.
[0022] The preparation method of the ZrO2 / γ-Al2O3 composite carrier of the present invention, wherein the heating temperature in step 4 is 70-85°C, the acid used for acid hydrolysis is an inorganic acid, and the pH of the system during the acid hydrolysis is 2-3.
[0023] The preparation method of the ZrO2 / γ-Al2O3 composite carrier of the present invention, wherein, in step 5, the pH value of the zirconium aluminum sol is adjusted to 9-10; the temperature of the vacuum freeze-drying is -15--30°C, the pressure is 10-30KPa, and the time is 24-50h.
[0024] The preparation method of the ZrO2 / γ-Al2O3 composite carrier described in the present invention, wherein the auxiliary agent in step 6 is a binder and a lubricant, the binder is selected from at least one of nitric acid, citric acid, oxalic acid, and tartaric acid, and the lubricant is selected from at least one of sesbania powder, dry starch, graphite, and paraffin; the amount of the auxiliary agent added is 1 to 5wt% of the mass of the zirconium-aluminum composite material.
[0025] In order to achieve the above object, the present invention also provides a ZrO2 / γ-Al2O3 composite carrier obtained by the preparation method of the above ZrO2 / γ-Al2O3 composite carrier.
[0026] The ZrO2 / γ-Al2O3 composite carrier of the present invention has a specific surface area of 260 to 380 m 2 / g, pore volume 0.6~1.0cm 3 / g.
[0027] In order to achieve the above object, the present invention further provides a selective hydrodesulfurization catalyst including a carrier and an active component, wherein the carrier is the above ZrO2 / γ-Al2O3 composite carrier.
[0028] The selective hydrodesulfurization catalyst of the present invention, wherein the active components include MoO3 and NiO, based on the total mass of the selective hydrodesulfurization catalyst, the loading amount of the active component MoO3 is 20-26wt%, and the loading amount of the NiO is 2-4.5wt%.
[0029] In order to achieve the above object, the present invention further provides a diesel hydrodesulfurization method, and the catalyst used is the above selective hydrodesulfurization catalyst.
[0030] Beneficial effects of the present invention:
[0031] The invention introduces heteroatom zirconium with a suitable electronic structure, which can affect the formation of the active phase, change the morphology of the active phase, and form an active phase that is conducive to the endpoint adsorption of complex sulfides, thereby improving the DDS selectivity of the catalyst, allowing diesel to mainly remove sulfur from sulfur-containing species in a direct desulfurization manner, and giving full play to the advantages of low reaction severity and low hydrogen consumption of the DDS pathway.
[0032] The heteroatom zirconium introduced in the present invention can weaken the interaction between the hydrogenation metal and the carrier, which is beneficial to the formation of a highly active multilayer active phase and improves the catalyst's hydrodesulfurization, denitrogenation activity and aromatics saturation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a high-resolution transmission electron micrograph HRTEM of the catalyst in Example 2 of the present invention after sulfurization. DETAILED DESCRIPTION
[0034] The following is a detailed description of the embodiments of the present invention. The embodiments are implemented based on the technical solution of the present invention, and detailed implementation methods and processes are given. However, the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments where specific conditions are not specified are usually based on conventional conditions.
[0035] The present invention discloses a method for preparing a ZrO2 / γ-Al2O3 composite carrier, comprising the following steps:
[0036] Step 1, mixing zirconium oxychloride and water to obtain a zirconium-containing solution;
[0037] Step 2, adjusting the pH value of the zirconium-containing solution to alkaline, stirring, and aging;
[0038] Step 3, separating the aged material obtained in step 2 to obtain a solid, and washing to remove Cl in the obtained solid. -, obtaining a zirconium-containing hydrogel;
[0039] Step 4, mixing sucrose, pseudo-boehmite, the zirconium-containing hydrogel and water, heating, and acid-lyzing to obtain zirconium-aluminum sol;
[0040] Step 5, adjusting the pH value of the zirconium-aluminum sol to alkaline, aging, then washing with water to neutrality, solid-liquid separation, and vacuum freeze-drying to obtain a zirconium-aluminum composite material;
[0041] Step 6: Mix the zirconium-aluminum composite material with an additive, and shape it to obtain a ZrO2 / γ-Al2O3 composite carrier.
[0042] The method of the present invention can introduce heteroatomic zirconium with a suitable electronic structure, affect the electronic configuration and lattice structure of the Ni-Mo-S active phase, make its reactive sites with sulfur-containing compounds protrude from the active phase plane, thereby weakening the steric hindrance in the adsorption process of complex sulfides and active sites, realize the end point adsorption of both, and strengthen the DDS path of complex sulfides. Give full play to the advantages of low reaction severity and low hydrogen consumption of the DDS path.
[0043] Sucrose is added in the method of the present invention. Sucrose molecules contain multiple hydroxyl groups, and the molecules can form an aggregate similar to surfactant micelles through hydrogen bonding. At the same time, the pseudo-boehmite sol particles themselves also contain multiple hydroxyl groups, and the aluminum species can form an organic-inorganic mesophase with the aggregates formed by the sucrose molecules through hydrogen bonding, so that the obtained carrier forms a mesoporous structure.
[0044] At the same time, in step 5 of the present invention, the zirconium-aluminum composite material is obtained by vacuum freeze-drying, which can avoid the problems of reduced mechanical strength of the zirconium-aluminum composite material caused by conventional drying.
[0045] In one embodiment, step 1 is to add zirconium oxychloride to water and stir until fully dissolved to obtain a zirconium-containing solution. The molecular formula of the zirconium oxychloride of the present invention is ZrOCl2·8H2O. In another embodiment, the concentration of the zirconium-containing solution is 0.18-0.24 mol / L.
[0046] In one embodiment, step 2 is: adjusting the pH value of the zirconium-containing solution to 9-10, then stirring for 0.5-2 hours, and aging for 2-8 hours, wherein the aging temperature is, for example, room temperature. The present invention does not particularly limit the reagent used to adjust the pH value of the zirconium-containing solution, such as ammonia water.
[0047] In one embodiment, step 3 is: separating the material obtained in step 2 to obtain a solid, washing the solid with deionized water to remove Cl in the solid. - The present invention does not particularly limit the separation method of the material obtained in step 2, as long as the liquid and the solid can be basically separated, such as suction filtration, centrifugation, etc.
[0048] In one embodiment, step 4 is: adding sucrose, pseudo-boehmite and zirconium-containing hydrogel into water with a solid-liquid mass ratio of 1:5 to 20, stirring and mixing, and then heating the mixture to 70 to 85°C, further, for example, 80 to 85°C, stirring while adding inorganic acid, adjusting the pH of the system to 2 to 3, and acid hydrolyzing at a constant temperature for 4 to 8 hours to form a zirconium aluminum sol.
[0049] In another embodiment, the amount of sucrose added is 5 to 15 wt% of the weight of the ZrO2 / γ-Al2O3 composite support, the amount of pseudo-boehmite added in terms of alumina is 80 to 95 wt% of the weight of the ZrO2 / γ-Al2O3 composite support, and the amount of zirconium oxychloride added in terms of zirconium dioxide is 5 to 20 wt% of the weight of the ZrO2 / γ-Al2O3 composite support.
[0050] The inorganic acid is, for example, one or more of hydrochloric acid, sulfuric acid, and nitric acid.
[0051] In one embodiment, step 5 is: adjusting the pH value of the zirconium aluminum sol to 9-10, aging for 2-10 hours after forming a gel, then washing with water until neutral, solid-liquid separation, and vacuum freeze-drying to obtain a zirconium aluminum composite material.
[0052] The present invention does not particularly limit the reagent for adjusting the pH value of the zirconium aluminum sol, for example, ammonia water. The present invention does not particularly limit the method of solid-liquid separation in step 5, for example, filtration, vacuum filtration, centrifugation, etc. The aging temperature of the present invention is, for example, room temperature.
[0053] In one embodiment, the vacuum freeze drying temperature of the present invention is -15 to -30°C, the pressure is 10 to 30 KPa, and the time is 24 to 50 hours. The vacuum freeze drying of the present invention can avoid the problems of reduced mechanical strength and the like that occur in conventional drying of the zirconium-aluminum composite material, and can make the zirconium-aluminum composite material have a pore structure suitable for diesel hydrodesulfurization reaction.
[0054] In one embodiment, step 6 is: mixing the zirconium-aluminum composite material with an additive, forming, and then drying and calcining to obtain a ZrO2 / γ-Al2O3 composite carrier.
[0055] Wherein, the additive in step 6 is, for example, a binder and a lubricant, the binder is, for example, selected from at least one of nitric acid, citric acid, oxalic acid, and tartaric acid, and the lubricant is, for example, selected from at least one of sesbania powder, dry starch, graphite, and paraffin. In another embodiment, the additive is added in an amount of 1 to 5 wt% of the mass of the zirconium-aluminum composite material.
[0056] The present invention does not particularly limit the conditions of drying and calcining. For example, the calcining temperature is preferably 400 to 600° C., and the calcining time is preferably 2 to 6 hours.
[0057] Thus, the present invention adopts the above method to obtain a ZrO2 / γ-Al2O3 composite carrier, in which the content of zirconium oxide is 5-20wt% and the content of aluminum oxide is 80-95wt%. The present invention does not particularly limit the shape of the composite carrier, such as a clover shape, a tooth ball shape, a four-leaf clover shape or a granular shape. The composite carrier obtained by the method of the present invention has a high specific surface area, a large pore volume, good stability, and high mechanical strength. The specific surface area of the composite carrier is generally 260-380m 2 / g, the pore volume is generally 0.6~1.0cm 3 / g.
[0058] The ZrO2 / γ-Al2O3 composite carrier can be used to prepare a selective hydrodesulfurization catalyst, the active components of which include, for example, molybdenum and nickel, more specifically, MoO3 and NiO. In one embodiment, based on the total mass of the selective hydrodesulfurization catalyst, the loading amount of the active component MoO3 is 20 to 26 wt%, and the loading amount of the NiO is 2 to 4.5 wt%.
[0059] The present invention does not particularly limit the preparation method of the selective hydrodesulfurization catalyst. For example, the ZrO2 / γ-Al2O3 composite carrier is impregnated in a solution containing an active component precursor by an impregnation method, and then filtered, dried, and calcined to obtain a selective hydrodesulfurization catalyst.
[0060] In one embodiment, the active component precursor is a molybdenum-containing compound and a nickel-containing compound, more specifically, ammonium molybdate, nickel nitrate, ammonium phosphomolybdate, nickel chloride and nickel acetate. The active component precursor is dissolved in water, ethanol or ammonia to form a solution containing the active component precursor.
[0061] The present invention does not particularly limit the impregnation method, for example, it can be equal volume negative pressure impregnation.
[0062] In the selective hydrodesulfurization catalyst obtained by the method of the present invention, the zirconium oxide in the composite carrier can weaken the strong interaction between the active component and the carrier, making the active metal easy to reduce, and can more effectively play the role of the zirconium oxide, synergistically adjust the physical and chemical properties and pore structure of the carrier surface, so that the catalyst has higher catalytic activity.
[0063] The catalyst prepared by the present invention has high hydrodesulfurization and aromatic saturation activity and low hydrogen consumption. The sulfur in diesel with a sulfur content of 12300ppm and a polycyclic aromatic hydrocarbon content of 14.9wt% can be removed to less than 10ppm, and the polycyclic aromatic hydrocarbon content can be removed to less than 7wt%, so that the diesel hydrogenation product meets the National VI clean diesel standard. The hydrogen consumption is reduced by 3-7wt%, and the catalyst has good stability, which can provide technical support for the hydrogenation unit to achieve the goal of "five-year repair" or even a longer operation cycle.
[0064] When the selective hydrodesulfurization catalyst of the present invention is used for intermediate distillate oil, especially diesel hydrodesulfurization, it mainly removes sulfur in sulfur-containing species in a direct desulfurization manner, thereby reducing the hydrogen consumption in the desulfurization process.
[0065] The technical solution of the present invention will be further described in detail below through specific embodiments.
[0066] Example 1
[0067] Add 78 g of ZrOCl2·8H2O to a container containing 1000 ml of deionized water, stir until fully dissolved, slowly dropwise add to the diluted ammonia water, adjust the pH value to 9, stir for 1 h, age for 6 h, filter, and wash the Cl in the solid with deionized water. - , and a zirconium-containing hydrogel was obtained. 15g of sucrose, 393g of pseudo-boehmite (dry basis 70wt%, the same below) and the obtained zirconium-containing hydrogel were added to deionized water, with a solid-liquid mass ratio of 1:15, and stirred to mix well. Then the mixture was heated to 80°C, and nitric acid was slowly added dropwise while stirring to adjust the pH of the system to 2, and acid hydrolyzed at constant temperature for 4h to form aluminum zirconium sol; then an appropriate amount of ammonia water was slowly added dropwise to adjust the pH of the aluminum zirconium sol to 9.5 to form a gel, aged for 10h, washed with deionized water to pH=7, filtered, freeze-dried at 10KPa and -15°C for 28h to obtain a zirconium-aluminum composite material, ground the composite material, passed through a 180-mesh sieve, added 2.5wt% of sesbania powder and 2.5wt% of nitric acid by mass of the zirconium-aluminum composite material, mixed evenly, and extruded, and then dried at 110°C for 2h and calcined at 500°C for 4h to obtain a ZrO2 / γ-Al2O3 composite carrier, whose main properties are listed in Table 1.
[0068] After the carrier preparation was completed, a nickel-molybdenum supported catalyst was prepared by an equal volume impregnation method, wherein the loading amounts of MoO3 and NiO were 25wt% and 3.5wt%, respectively.
[0069] Example 2
[0070] Add 62 g of ZrOCl2·8H2O to a container containing 1000 ml of deionized water, stir until fully dissolved, slowly dropwise add to the diluted ammonia water, adjust the pH value to 10, stir for 2 h, age for 6 h, filter, and wash the Cl in the solid with deionized water. -, and obtain a zirconium-containing hydrogel. 12g of sucrose, 139g of pseudo-boehmite and the obtained zirconium-containing hydrogel are added to deionized water with a solid-liquid mass ratio of 1:15, and stirred to mix well. Then the mixture is heated to 80°C, and nitric acid is slowly added while stirring to adjust the pH of the system to 2.5, and acid hydrolyze at constant temperature for 4h; then an appropriate amount of ammonia water is slowly added to adjust the pH of the aluminum zirconium sol to 9 to form a gel, which is aged for 10h, washed with deionized water until pH=7, and filtered, freeze-dried at 10KPa and -15°C for 40h to obtain a zirconium-aluminum composite material, and the composite material is ground and passed through a 180-mesh sieve, and 2.5wt% of sesbania powder and 3wt% of nitric acid are added to the zirconium-aluminum composite material, mixed evenly, and extruded, and then dried at 110°C for 2h and calcined at 500°C for 4h to obtain a ZrO2 / γ-Al2O3 composite carrier, whose main properties are listed in Table 1. The catalyst preparation is the same as in Example 1.
[0071] Example 3
[0072] Add 74 g ZrOCl2·8H2O to a container containing 1000 ml of deionized water, stir until fully dissolved, slowly dropwise add to the diluted ammonia water, adjust the pH value to 9, stir for 1.5 h, age for 4 h, filter, and wash the Cl in the solid with deionized water. - , and obtain a zirconium-containing hydrogel. 16g of sucrose, 249g of pseudo-boehmite and the obtained zirconium-containing hydrogel are added to deionized water with a solid-liquid mass ratio of 1:15, and stirred to mix well. Then the mixture is heated to 80°C, and nitric acid is slowly added while stirring to adjust the pH of the system to 2.5, and acid hydrolyze at constant temperature for 4h; then an appropriate amount of ammonia water is slowly added to adjust the pH of the aluminum zirconium sol to 9 to form a gel, which is aged for 10h, washed with deionized water until pH=7, and filtered, freeze-dried at 20KPa and -20°C for 48h to obtain a zirconium-aluminum composite material, and the composite material is ground and passed through a 180-mesh sieve, and 2.5wt% of sesbania powder and 3wt% of nitric acid are added to the zirconium-aluminum composite material, mixed evenly, and extruded, and then dried at 110°C for 2h and calcined at 500°C for 4h to obtain a ZrO2 / γ-Al2O3 composite carrier, whose main properties are listed in Table 1. The catalyst preparation is the same as in Example 1.
[0073] Example 4
[0074] Add 58 g of ZrOCl2·8H2O to a container containing 1000 ml of deionized water, stir until fully dissolved, slowly dropwise add to the diluted ammonia water, adjust the pH value to 10, stir for 2 h, age for 6 h, filter, and wash the Cl in the solid with deionized water. -, and obtain a zirconium-containing hydrogel. 14g of sucrose, 113g of pseudo-boehmite and the obtained zirconium-containing hydrogel are added to deionized water with a solid-liquid mass ratio of 1:15, and stirred to mix well. Then the mixture is heated to 80°C, and nitric acid is slowly added while stirring to adjust the pH of the system to 2, and acid hydrolyzed at constant temperature for 4h; then an appropriate amount of ammonia water is slowly added to adjust the pH of the aluminum zirconium sol to 9.5 to form a gel, aged for 10h, washed with deionized water to pH=7, filtered, freeze-dried at 10KPa and -20°C for 36h, and a zirconium-aluminum composite material is obtained. The composite material is ground, passed through a 180-mesh sieve, 2.5wt% sesbania powder and 3wt% nitric acid of the zirconium-aluminum composite material are added, mixed evenly, and extruded, and then dried at 110°C for 2h and calcined at 500°C for 4h to obtain a ZrO2 / γ-Al2O3 composite carrier, whose main properties are listed in Table 1. The catalyst preparation is the same as in Example 1.
[0075] Comparative Example 1
[0076] Add 20ml silica gel (SiO2 content 25wt%) to 100ml aluminum nitrate (2mol / L) solution, mix evenly, heat the solution to 60℃, add ammonia water to adjust the solution pH to 7, and obtain aluminum sol. Prepare 0.1mol / L zirconium nitrate solution, heat to 95℃, add oxalic acid to the solution, adjust the solution pH to 5.5, and keep constant temperature for 2h to obtain zirconium sol. Mix zirconium sol, aluminum sol and deionized water in a volume ratio of 1:2 and stir for 2h, heat to 50℃ and keep constant temperature for 2h, add 200ml ethanol and filter, wash with deionized water, and dry to obtain composite oxide dry glue. Grind the composite oxide dry glue, pass through a 180 mesh sieve, add 2wt% sesbania powder and 3wt% nitric acid to the composite oxide dry glue, mix evenly, and then extrude and shape, then dry at 110℃ for 2h, and calcine at 500℃ for 4h to obtain ZrO2 / γ-Al2O3 composite carrier, whose main properties are listed in Table 1. The catalyst preparation is the same as Example 1.
[0077] Catalyst evaluation
[0078] The catalysts obtained in the above examples and comparative examples were subjected to hydrotreating performance evaluation in a 200 ml fixed bed reactor. The crude oil treated by the above catalysts (properties shown in Table 2) was the same as the experimental conditions, reaction temperature 350°C, hydrogen partial pressure 6.0 MPa, space velocity 1.0 h -1 , hydrogen-to-oil ratio 500:1, and the catalyst activity evaluation data are shown in Table 3.
[0079] Table 1 shows the structural characteristics and strength property data of the composite carriers obtained in Examples 1 to 4 and Comparative Example 1.
[0080] Table 1 Physical properties of composite carrier
[0081]
[0082] As shown in Table 1, the specific surface area and pore volume of the composite carriers obtained in Examples 1 to 4 are greater than those obtained in Comparative Example 1, and the mechanical strength of the composite carriers obtained in Examples 1 to 4 is higher than that in Comparative Example 1.
[0083] Table 2 Raw oil properties
[0084] project Straight run diesel <![CDATA[Density (20 °C), kg / m 3 > 843 Nitrogen content, ppm 92 Sulfur content, ppm 12300 PAHs, wt% 14.9
[0085] Table 3 Catalyst hydrogenation evaluation results
[0086]
[0087] As shown in Table 3, the hydrodesulfurization activity and aromatic saturation performance of the catalysts provided in Examples 1-4 of the present invention are higher than those of the catalyst in Comparative Example 1, and the hydrogen consumption is lower than that of Comparative Example 1. Compared with the HYD path, the DDS path has the advantages of low hydrogen consumption and low severity. Under the same reaction conditions, processing the same raw materials, and the hydrogenation products reach the same indicators, the chemical hydrogen consumption of the DDS path is low, which can save hydrogen resources and reduce the production cost of oil products. It can be seen from the hydrogen consumption data in Table 3 that the catalyst of the present invention can promote the hydrogenation reaction to proceed along the DDS path.
[0088] Figure 1 This is a high-resolution transmission electron micrograph HRTEM of the catalyst in Example 2 after sulfurization. Figure 1 The morphology of the active components of the catalyst can be observed. MoS2 microcrystals are evenly distributed on the catalyst surface, with more grain layers and shorter lengths. Most of them are short crystal structures with 3 to 5 layers of plates. Therefore, its active structure has more coordination unsaturated edge sites and edge sites, which makes the catalyst have higher hydrodesulfurization activity and aromatic saturation performance.
[0089] For supported catalysts, the carrier has an important influence on the catalytic performance of the catalyst. The present invention introduces heteroatom zirconium with a suitable electronic structure, adds sucrose and combines it with a vacuum freeze-drying process to prepare a ZrO2 / γ-Al2O3 composite carrier with a large specific surface area and pore volume, good stability and high mechanical strength. The electronic configuration and lattice structure of the Ni-Mo-S active phase are affected, so that the active sites of its reaction with sulfur-containing compounds protrude from the active phase plane, thereby weakening the steric hindrance in the adsorption process of complex sulfides and active sites, achieving the end-point adsorption of the two, and strengthening the DDS path of complex sulfides.
[0090] In summary, the composite carrier and catalyst prepared by the present invention have the following advantages:
[0091] (1) The composite carrier has high specific surface area, large pore volume, good stability and high mechanical strength, and is suitable as a catalyst carrier for hydrotreating of intermediate distillates.
[0092] (2) The zirconium oxide in the composite carrier can weaken the strong interaction between the active component and the carrier, making the active metal easy to reduce and giving full play to the advantages of the zirconium oxide active carrier.
[0093] (3) The catalyst prepared by the present invention has high hydrodesulfurization and aromatic saturation activity and low hydrogen consumption. The sulfur in diesel with a sulfur content of 12300ppm and a polycyclic aromatic hydrocarbon content of 14.9wt% can be removed to less than 10ppm, and the polycyclic aromatic hydrocarbon content can be removed to less than 7wt%, and the product meets the National VI clean diesel standard. The hydrogen consumption is reduced by 3-7wt%, and the catalyst has good stability, which can provide technical support for the hydrogenation unit to achieve the goal of "five-year repair" or even longer operation cycle.
[0094] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a ZrO2 / γ-Al2O3 composite carrier, characterized in that: The steps include: Step 1, mixing zirconium oxychloride and water to obtain a zirconium-containing solution; Step 2, adjusting the pH value of the zirconium-containing solution to alkaline, stirring, and aging; Step 3, separating the aged material obtained in step 2 to obtain a solid, and washing to remove Cl in the obtained solid. - , obtaining a zirconium-containing hydrogel; Step 4, mixing sucrose, pseudo-boehmite, the zirconium-containing hydrogel and water, heating, and acid-lyzing to obtain zirconium-aluminum sol; Step 5, adjusting the pH value of the zirconium-aluminum sol to alkaline, aging, then washing with water to neutrality, solid-liquid separation, and vacuum freeze-drying to obtain a zirconium-aluminum composite material; Step 6: Mix the zirconium-aluminum composite material with an additive, and shape it to obtain a ZrO2 / γ-Al2O3 composite carrier.
2. The method for preparing the ZrO2 / γ-Al2O3 composite carrier according to claim 1, characterized in that: In step 1, the concentration of the zirconium-containing solution is 0.18-0.24 mol / L; in step 2, the pH value of the zirconium-containing solution is adjusted to 9-10, and the adjusting reagent is ammonia water.
3. The method for preparing the ZrO2 / γ-Al2O3 composite carrier according to claim 1, characterized in that: The amount of sucrose added is 5 to 15 wt% of the weight of the ZrO2 / γ-Al2O3 composite carrier; the amount of pseudo-boehmite added in terms of alumina is 80 to 95 wt% of the weight of the ZrO2 / γ-Al2O3 composite carrier; the amount of zirconium oxychloride added in terms of zirconium dioxide is 5 to 20 wt% of the weight of the ZrO2 / γ-Al2O3 composite carrier.
4. The method for preparing the ZrO2 / γ-Al2O3 composite carrier according to claim 1, characterized in that: The heating temperature in step 4 is 70-85° C., the acid used for acid hydrolysis is an inorganic acid, and the pH of the system during the acid hydrolysis is 2-3.
5. The method for preparing the ZrO2 / γ-Al2O3 composite carrier according to claim 1, characterized in that: Step 5: adjusting the pH value of the zirconium aluminum sol to 9-10; the vacuum freeze drying temperature is -15--30°C, the pressure is 10-30KPa, and the time is 24-50h.
6. The method for preparing the ZrO2 / γ-Al2O3 composite carrier according to claim 1, characterized in that: In step 6, the auxiliary agents are a binder and a lubricant, the binder is selected from at least one of nitric acid, citric acid, oxalic acid, and tartaric acid, and the lubricant is selected from at least one of sesbania powder, dry starch, graphite, and paraffin; the amount of the auxiliary agent added is 1 to 5 wt% of the mass of the zirconium-aluminum composite material.
7. A ZrO2 / γ-Al2O3 composite carrier obtained by the preparation method of the ZrO2 / γ-Al2O3 composite carrier according to any one of claims 1 to 6.
8. The ZrO2 / γ-Al2O3 composite carrier according to claim 7, characterized in that: The specific surface area of the composite carrier is 260 to 380 m 2 / g, pore volume 0.6~1.0cm 3 / g.
9. A selective hydrodesulfurization catalyst, characterized in that: It comprises a carrier and an active component, wherein the carrier is the ZrO2 / γ-Al2O3 composite carrier as claimed in claim 7.
10. The selective hydrodesulfurization catalyst according to claim 9, characterized in that The active components include MoO3 and NiO. Based on the total mass of the selective hydrodesulfurization catalyst, the loading amount of the active component MoO3 is 20-26 wt%, and the loading amount of the NiO is 2-4.5 wt%.
11. A diesel hydrodesulfurization method, characterized in that: The catalyst used is the selective hydrodesulfurization catalyst according to claim 9 or 10.
Citation Information
Patent Citations
Alumina-zirconia composite carrier and preparation method thereof
CN102247896B
Method for preparing zirconia-alumina composite oxide carrier
CN102451764A
Alumina-zirconia-titania composite carrier and its preparation method
CN102989518B
Diesel hydrodesulfurization and denitrification catalyst and preparation method thereof
CN103551162A
Composite catalyst carrier containing zirconium oxide as well as preparation method and application thereof
CN108855048A